2016
DOI: 10.1007/s13157-016-0819-7
|View full text |Cite
|
Sign up to set email alerts
|

Blue Carbon Stock of the Bangladesh Sundarban Mangroves: What could Be the Scenario after a Century?

Abstract: The total blue carbon stock of the Bangladesh Sundarban mangroves was evaluated and the probable future status after a century was predicted based on the recent trend of changes in the last 30 years and implementing a hybrid model of Markov Chain and Cellular automata. At present 36.24 Tg C and 54.95 Tg C are stored in the above-ground and below-ground compartments respectively resulting in total blue carbon stock of 91.19 Tg C. According to the prediction 15.88 Tg C would be lost from this region by the year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This value was higher than those reported for subtropical mixed mangrove forest at Ishigaki Island, southern Japan (78.6 Mg•ha −1 ; Suzuki and Tagawa 1983). The present value of accumulation of mean aboveground biomass was within the converted range of AGB from aboveground biomass carbon for Sundarbans mangrove forests (55.3-153.4 Mg•ha −1 C; Chanda et al 2016). Compared to the previous studies, the present study indicates that biomass productivity of the mangrove species in the present study was relatively high among the mangrove forests in the tropical and subtropical areas, showing that mean annual wood production of 7.1 Mg•ha −1 •yr −1 .…”
Section: Aboveground and Belowground Biomasssupporting
confidence: 59%
“…This value was higher than those reported for subtropical mixed mangrove forest at Ishigaki Island, southern Japan (78.6 Mg•ha −1 ; Suzuki and Tagawa 1983). The present value of accumulation of mean aboveground biomass was within the converted range of AGB from aboveground biomass carbon for Sundarbans mangrove forests (55.3-153.4 Mg•ha −1 C; Chanda et al 2016). Compared to the previous studies, the present study indicates that biomass productivity of the mangrove species in the present study was relatively high among the mangrove forests in the tropical and subtropical areas, showing that mean annual wood production of 7.1 Mg•ha −1 •yr −1 .…”
Section: Aboveground and Belowground Biomasssupporting
confidence: 59%
“…The Bangladesh Sundarbans is situated between 21º30' N and 22º30' N and 89º00' E and 89º55' E. The climate of the Sundarbans is warm, humid, and tropical, where annual precipitation varies from 1474 to 2265 mm and mean annual minimum and maximum temperature is between 29 o C to 31 o C (Chowdhury et al, 2016;Sarker et al, 2016). Based on the salinity variation, the Sundarbans naturally divides into three distinct zones based on the soil salinity; i) Oligohaline (LSZ) (<2 dS/m, ii) Mesohaline (2-4 dS/m) and iii) Polyhaline (>4 dS/m) (Siddiqi, 2001;Chanda et al, 2016b). Several studies have identified a relationship between tree species abundance along the east-west salinity gradient (Iftekhar and Saenger, 2008;Aziz and Paul, 2015;Sarker et al, 2016;Sarker et al, 2019a).…”
Section: Study Areamentioning
confidence: 99%
“…Sundarbans mangrove forest, Bangladesh. Legend colour represents three major salinity zones (Chanda et al, 2016b). ESRI Basemap Sources: Esri, HERE, Garmin, FAO, NOAA, USGS, © OpenStreetMap contributors, and the GIS User Community.…”
mentioning
confidence: 99%
“…Detailed data on district-wise spatial distribution of existing carbon studies have been provided in Supplementary material 3. (Chanda et al, 2016). Even though species richness limits the use of species-specific allometric equations (Mizanur, Khan, Hoque, & Ahmed, 2015), the use of common equations of other countries will yield unreasonable estimates which posed doubt on the accuracy of national estimation (Ahiduzzaman and Islam, 2016;Mizanur et al, 2015).…”
Section: Forest Areas Covered: Spatial Distribution Of Existing Studiesmentioning
confidence: 99%